Pengaruh Lama Pengeringan Cabinet Drying Terhadap Karakteristik Kimia dan Organoleptik Manisan Kering Pala Banda - Ramalan, Aprillianti; Tetelepta, Gilian; Polnaya, Febby J (Universitas Pattimura, 2024)
The research aimed to determine the proper drying time to produce dried sweets banda nutmeg with the best chemical and organoleptic properties. This study used a completely randomized design with one factorial with four treatment levels: sun drying, drying cabinet dryer 18, 19, and 20 hours. The parameters analyzed were chemical tests (moisture content, ash content, and total sugar) and organoleptic tests (color, aroma, taste, texture, overall). The results showed that treatment with a drying time of 18 hours produced the best-sweets banda nutmeg with chemical characteristics of 11.44% water content, 0.84% ​​ash content, 45.89% total sugar, and based on the hedonic organoleptic test showed like color (3 .20), liking (3.04), liking texture (3.08). In contrast, for hedonic quality, it offers a brown-yellow color (2.48), nutmeg flavor (3.36), and slightly chewy texture (2.16 ).